Diversification of function by different isoforms of conventionally shared RNA polymerase subunits. - Devaux, S; Kelly, S; Lecordier, L; Wickstead, B; Perez-Morga, D; Pays, E; Vanhamme, L; Gull, K (2007)
Eukaryotic nuclei contain three classes of multisubunit DNA-directed RNA polymerase. At the core of each complex is a set of 12 highly conserved subunits of which five--RPB5, RPB6, RPB8, RPB10, and RPB12--are thought to be common to all three polymerase classes. Here, we show that four distantly related eukaryotic lineages (the higher plant and three protistan) have independently expanded their repertoire of RPB5 and RPB6 subunits. Using the protozoan parasite Trypanosoma brucei as a model organism, we demonstrate that these distinct RPB5 and RPB6 subunits localize to discrete subnuclear compartments and form part of different polymerase complexes. We further show that RNA interference-mediated depletion of these discrete subunits abolishes class-specific transcription and hence demonstrates complex specialization and diversification of function by conventionally shared subunit groups.